Maximum entanglement of formation for a two-mode Gaussian state over passive operations - Tserkis, Spyros (2020)
We quantify the maximum amount of entanglement of formation (EoF) that can be achieved by continuous-variable states under passive operations, which we refer to as the EoF potential. Focusing, in particular, on two-mode Gaussian states we derive analytical expressions for the EoF potential for specific classes of states. For more general states, we demonstrate that this quantity can be upper bounded by the minimum amount of squeezing needed to synthesize the Gaussian modes, a quantity called squeezing of formation. Our work, thus, provides a link between nonclassicality of quantum states and the nonclassicality of correlations.